Methodological foundations for assessing the balance of sustainable development of regional economies in the context of innovation activity - S. V. Simonov (Вестник университета, 2025)
In the current difficult economic conditions, methodological foundations for assessing the balance of sustainable development of regional economies, together with the introduction and application of innovative activity and innovative technologies, are of the purpose of the work for the development of the regional economy. When assessing the balance of the sustainable development of the regional economies in the context of the innovation activity, the directions for the application of various methodological techniques are identified, which are based on the analysis of ratings of complex indicators and assessment of the level of their implementation. This process is unambiguous. The conducted research is aimed at developing various methodological techniques for assessing the balance of the sustainable development of the   regional economies in the context of the innovation activity. The leading approach (or method) to the study of this problem is the assessment of the sustainability rating of regional economic systems. The calculation is based on the complex indicators, the impact of which contributes to an increase in the rating of regions with an indispensable balanced functioning. The conclusion of the study is formulated on the materials of scientists who have   studied and are studying the problem under consideration: the process of an effective approach to the balanced development of the regional economic systems is based on integrity, divided into its structural elements.